Effect of alkali treatment and radicle removal on the quality of sor ghum malt and obushera - Tabula, Arthur (Kampala, 2015)
Unpublished dissertation (Msc. FST) - Makerere University, 2015
Includes bibliographical references (p. 45-54).
Keywords: Sorghum products